设\( {\bf{A}} \) 为三阶矩阵,\( { { \bf{A}}^*} \)是\( {\bf{A}} \)的伴随矩阵,且\( \left| {\bf{A}} \right| = 1 \),则\( \left| {2 { { \bf{A}}^{ - 1}} + 3 { { \bf{A}}^*}} \right| = \)______
设\( {\bf{A}} \) 为三阶矩阵,\( { { \bf{A}}^*} \)是\( {\bf{A}} \)的伴随矩阵,且\( \left| {\bf{A}} \right| = 1 \),则\( \left| {2 { { \bf{A}}^{ - 1}} + 3 { { \bf{A}}^*}} \right| = \)______
${\bf P}(X=-2)=\,$ ${\bf P}(X=1)=\,$ ${\bf P}(X=0)=\,$______
${\bf P}(X=-2)=\,$ ${\bf P}(X=1)=\,$ ${\bf P}(X=0)=\,$______
${\bf P}(X=4)=\,$ ${\bf P}(X=3)=\,$ ${\bf P}(X=2)=\,$ ${\bf P}(X=1)=\,$______
${\bf P}(X=4)=\,$ ${\bf P}(X=3)=\,$ ${\bf P}(X=2)=\,$ ${\bf P}(X=1)=\,$______
${\bf P}(X=2)=\,$ ${\bf P}(X=1)=\,$______
${\bf P}(X=2)=\,$ ${\bf P}(X=1)=\,$______
串函数StrCmp(“abA”,”aba”)的值为()。 A: 1 B: 0 C: “abAaba” D: -1
串函数StrCmp(“abA”,”aba”)的值为()。 A: 1 B: 0 C: “abAaba” D: -1
串函数StrCmp("abA","aba")的值为()。 A: 1 B: 0 C: "abAaba" D: -1
串函数StrCmp("abA","aba")的值为()。 A: 1 B: 0 C: "abAaba" D: -1
串函数StrCmp("abA","aba")的值为()。 A: 1 B: 0 C: "abAaba" D: -1
串函数StrCmp("abA","aba")的值为()。 A: 1 B: 0 C: "abAaba" D: -1
串函数StrCmp(“abA”,”aba”)的值为( )。 A: 1 B: 0 C: “abAaba” D: -1
串函数StrCmp(“abA”,”aba”)的值为( )。 A: 1 B: 0 C: “abAaba” D: -1
串函数StrCmp(“abA”,”aba”)的值为()。 A: 1 B: 0 C: “abAaba” D: -1
串函数StrCmp(“abA”,”aba”)的值为()。 A: 1 B: 0 C: “abAaba” D: -1
${\rm var}(X)=\,$ ${\bf E}[X]=\,$ ${\bf P}(X=3)=\,$ ${\bf P}(X=-2)=\,$ ${\bf P}(X=1)=\,$ ${\bf P}(X=0)=\,$______
${\rm var}(X)=\,$ ${\bf E}[X]=\,$ ${\bf P}(X=3)=\,$ ${\bf P}(X=-2)=\,$ ${\bf P}(X=1)=\,$ ${\bf P}(X=0)=\,$______